Designing a novel demand side regulation algorithm to participate in frequency control using iterated mappings. Issue 10 (1st October 2014) - Dehghanpour, Kaveh; Afsharnia, Saeed
Abstract : This study proposes a local and decentralised load management procedure to provide frequency control support in power systems, without a complex communication network. In this context, the authors aim is to design and develop a new and innovative control algorithm using iterated mappings. Iterated mappings are obtained by local frequency measurements and are proved to be strong tools in dynamical deterministic systems' analysis. The proposed algorithm is capable of assigning relevant operational states to power system during power contingencies; control action will then be exerted on that basis, with a simple and easy to implement data processing procedure. Efficiency of the control method is then verified by simulations in MATLAB environment.